Fire and late-Holocene expansion of Quercus ilex and Pinus pinaster on Corsica - Carcaillet, Christopher; Barakat, Hala N.; Panaïotis, Christophe; Loisel, Roger (Journal of Vegetation Science, 1997)
Abstract. The natural origin of old Quercus ilex (holm oak) forests on the west coast of Corsica is a matter of dispute. This paper discusses the use of pedoanthracology, especially adapted to approach topics in palaeoecology requiring a high spatial precision. It also shows the importance of fire in vegetation change during the Holocene. Pedoanthracology relies on botanical identification and AMS 14C dating of micro-charcoal found in soil. Three test pits were dug in a forest currently protected within the ‘Man and Biosphere’ program. These pits yielded large quantities of charcoal. There is evidence that Pinus nigra ssp. laricio (laricio pine) and understorey heather species (Ericaceae) played an important role in the vegetation at the beginning of the Subatlantic (ca. 2500 BP). The importance of Pinus pinaster (maritime pine), Quercus ilex and a few mesophilic species increased between 2000 and 1000 BP. Charcoal fragments found in the soil show the role of fire in the vegetation changes recorded. The late expansion of P. pinaster results from a high fire frequency. The hypothesis proposed in the paper suggests that fires destroyed the remaining toxic humus that had accumulated during the millennia which preceded the arrival of Q. ilex to our study sites. The late development of holm oak forest is a combination of the migration of the species and the increase of fire frequency since 2500 BP, most probably resulting from slash-and-burn agriculture.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: charcoal; Evergreen mediterranean forest; Fango valley; human impact; MAB reserve; Quaternary ecology